Dampak Depresi Pada Generasi Z Akibat Broken Home - Humairah, Asysyfa Putri; Komalasari, Shanty (Character Jurnal Penelitian Psikologi, 2024)
In this modern era, the phenomenon of divided families, or what is known as a broken home, has become a significant social issue. Generation Z, who are growing up amidst rapid social and technological change, are particularly vulnerable to the psychological impacts caused by a broken home. This study aims to explore the impact of depression on generation Z due to broken home conditions. This research uses qualitative analysis methods with in-depth interviews and participatory observation of a number of generation Z respondents who come from broken homes. The results of the research show that generation Z who experience broken homes have higher levels of depression compared to the generation who come from intact families. The impacts of depression include decreased self-confidence, increased stress levels, difficulty in building healthy interpersonal relationships, and decreased academic achievement. Apart from that, generation Z in a broken home situation also faces challenges in developing self-identity and confidence in future romantic relationships. This study highlights the importance of psychological intervention and social support for generation Z who come from broken home families. Specially designed psychological and social support programs can help reduce the impact of depression on generation Z, facilitate their emotional growth, and prepare them to better face life's challenges. Apart from that, the results of this research also provide insight for practitioners, educators and parents to better understand the psychological needs of generation Z who experience broken homes, with the hope that this understanding can help create an environment that supports positive growth and development for them.